IMPLEMENTASI TEKNOLOGI SOLAR PANEL UNTUK PARIWISATA DAN PENGAIRAN DI TANGGULANGSI KULON PROGO - Utari, Evrita Lusiana; Mustiadi, Ikhwan; Irawati, Novi (Universitas Respati Yogyakarta, 2021)
The Indonesian government is empowering renewable energy as an alternative energy besides energy produced by natural gas. This is the idea to implement using renewable energy that will be utilized in the tourism area of Tanggulangsi Gate. This area is located in the Sidoharjo Samigaluh Kulon Progo region. Where this area is developing tourism is supported by natural scenery and cool air adds to the atmosphere in interesting tourist places to visit. In addition to the good scenery at Tanggulangsi, it also offers another tourist spot, namely the Vegetable Picking tour which is managed by KWT Tanggulangsi Mekar. Implement renewable energy that will be applied in the tourist area of Tanggulangsi Gate in the form of lighting, and for picking vegetables is implemented to irrigate agricultural land in order to help the community in caring for their plants. Methods of carrying out activities include surveys or field observations, socialization of activities, counseling, training, design and installation of tools.Keywords: Energy, Samigaluh, Solar Panel, Kulon Progo